2021
DOI: 10.1002/bies.202000245
|View full text |Cite
|
Sign up to set email alerts
|

Paraspeckle nuclear condensates: Global sensors of cell stress?

Abstract: Paraspeckles are nuclear condensates, or membranelees organelles, that are built on the long noncoding RNA, NEAT1, and have been linked to many diseases. Although originally described as constitutive structures, here, in reviewing this field, we develop the hypothesis that cells increase paraspeckle abundance as part of a general stress response, to aid pro-survival pathways. Paraspeckles increase in many scenarios: when cells transform from one state to another, become infected with viruses and bacteria, begi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 116 publications
(248 reference statements)
2
47
0
Order By: Relevance
“…However, recent studies found that MALAT1 can reduce the epigenetic silencing of viral transcription by regulating promoter-enhancer interactions to promote viral transcription and infection ( 39 ). In addition, other studies have shown that lncRNA NEAT1 controls RNA regulatory processes by forming nonmembranous organelle nuclear paraspeckles ( 40 ). Knockout of NEAT1 can enhance viral production by promoting the export of HIV-1 mRNA from the nucleus to the cytoplasm in HeLa cells ( 41 ).…”
Section: Regulation Of Lncrnas During the Sars-cov-2 Life Cyclementioning
confidence: 99%
“…However, recent studies found that MALAT1 can reduce the epigenetic silencing of viral transcription by regulating promoter-enhancer interactions to promote viral transcription and infection ( 39 ). In addition, other studies have shown that lncRNA NEAT1 controls RNA regulatory processes by forming nonmembranous organelle nuclear paraspeckles ( 40 ). Knockout of NEAT1 can enhance viral production by promoting the export of HIV-1 mRNA from the nucleus to the cytoplasm in HeLa cells ( 41 ).…”
Section: Regulation Of Lncrnas During the Sars-cov-2 Life Cyclementioning
confidence: 99%
“…NEAT1_1 is a ubiquitous, abundant, polyadenylated and highly conserved transcript (Nakagawa et al, 2011). In contrast, NEAT1_2, responsible for formation of membraneless nuclear paraspeckle structures, is not polyadenylated and expressed under specific conditions or in response to various forms of stress (Adriaens et al, 2019; McCluggage and Fox, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…NEAT1 is a necessary component of subnuclear paraspeckles (Fox et al, 2002; Hutchinson et al, 2007; McCluggage and Fox, 2021), which assemble when specific architectural proteins bind to nascent NEAT1_2 transcripts (Mao et al, 2011). Paraspeckles are nuclear condensates containing diverse gene regulatory proteins (McCluggage and Fox, 2021). They are often observed in cancer cells, (Adriaens et al, 2016), and are associated with poor prognosis (Li et al, 2018a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 33 Paraspeckles are nuclear condensates that increase with changes in the state of cells, including responses to stress. 52 Mature RPE cells are believed to remain in a non-proliferative state throughout life, but in specific disease conditions, such as retinal detachment or PVR, the RPE cells undergo EMT and start to proliferate. It is still unclear whether paraspeckles regulate the cell-cycle state change in RPE cells, but our findings suggest that paraspeckle-related proteins or RNAs might be potential mechanisms through which RPE cell proliferation might be regulated.…”
Section: Discussionmentioning
confidence: 99%